Entitlements/rights, dignity and liberal democracy. Against the backdrop of the text by Cardinal Gerhard Müller “The Popes as Guardians of Human Dignity” - Bogdan Szlachta (Chrześcijaństwo-Świat-Polityka)
The concept of human dignity has already been widely discussed. In his interesting contribution, Cardinal Gerhard Müller once again turned to this category to expound upon its significance for Catholic reflection, to draw attention to its role in the teachings of 20th century Popes, and to bring it to light in connection with the increasing disputes concerning the ability/validity of “improving human nature”. Historians of political thought are interested in these disputes, and see them - insofar as they are carried out by using categories developed mainly in Western reflection - not as new ones, but rather embedded in past polemics, referring to old approaches, notably those which are prevailing today. Against the backdrop of the aforementioned disputation, this paper aims to reveal the fundamental tensions between the dominant liberal tradition – which, as the paper argues, is heterogenous – and the approach favored by the Popes”.